X = -12 !!
so first rewrite the fraction
multiply both sides
move the constant to the right
change the signs
then you have your solution
20 and 22
You would create an equation that would simulate this situation and solve for x to find the first even integer. Then add 2 to x to find the second even integer.
The two containers hold 328 ounces at the they hold same amount of water.
<u>Step-by-step explanation:</u>
The equations below model the ounces of water, y, in each container after x minutes.
![y = 16x + 104](https://tex.z-dn.net/?f=y%20%3D%2016x%20%2B%20104)
![y = -2x^{2} +40x+160](https://tex.z-dn.net/?f=y%20%3D%20-2x%5E%7B2%7D%20%2B40x%2B160)
At the time after the start when the containers hold the same amount of water, the two equations must be equal.
⇒
The first step is to divide everything by 2 to make it simplified.
⇒ ![8 x + 52 = - x^2 +20 x + 80](https://tex.z-dn.net/?f=8%20x%20%2B%2052%20%3D%20-%20x%5E2%20%2B20%20x%20%2B%2080)
Now put everything on the left
.
![x^2 + 8 x - 20 x + 52 - 80 = 0](https://tex.z-dn.net/?f=x%5E2%20%2B%208%20x%20-%2020%20x%20%2B%2052%20-%2080%20%3D%200)
Add the like terms together to further reduce the equation
![x^2 - 12 x - 28 = 0](https://tex.z-dn.net/?f=x%5E2%20-%2012%20x%20-%2028%20%3D%200)
Factorizing the equation to find the roots of the equation.
Here, b = -12 and c = -28
where,
- b is the sum of the roots ⇒ -14 + 2 = -12
- c is the product of the roots ⇒ -14 × 2 = -28
- Therefore, (x-14) (x+2) = 0
- The solution is x = -2 or x = 14
Take x = 14 and substitute in any of the given two equations,
⇒ ![y = 16(14) + 104](https://tex.z-dn.net/?f=y%20%3D%2016%2814%29%20%2B%20104)
⇒ ![y =224+104](https://tex.z-dn.net/?f=y%20%3D224%2B104)
⇒ 328 ounces
∴ The two containers hold 328 ounces at the they hold same amount of water.